2010
DOI: 10.1037/a0015790
|View full text |Cite
|
Sign up to set email alerts
|

Top-down attentional control for distractor locations: The benefit of precuing distractor locations on target localization and discrimination.

Abstract: This study investigated the active inhibition of precued distractor locations. In this study, the distractor location was precued by an arrow. Experiment 1 indicated that a valid precue could facilitate target localization. Experiment 2 demonstrated that when conflict trials were included, the distractor precue benefit was eliminated. Experiment 3 further showed that active inhibition required time to operate. The distractor precue benefit was observed only when the stimulus onset asynchrony between the precue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(94 citation statements)
references
References 74 publications
10
79
0
Order By: Relevance
“…This may ultimately reflect a purely locationbased inhibition strategy, making the results of Experiment 4 similar to other demonstrations of explicit location-based inhibition (Chao, 2010;Munneke et al, 2008), while extending these results by demonstrating a limitation in the number of locations that can be simultaneously suppressed. The fact that observers would adopt such an inefficient strategy strongly suggests that they were unable to explicitly tap into a purely feature-based inhibitory mechanism, even though such a mechanism does exist and is used implicitly in certain situations (e.g., the distractor-previewing effect).…”
Section: Inhibition Of Features and Locationssupporting
confidence: 81%
See 1 more Smart Citation
“…This may ultimately reflect a purely locationbased inhibition strategy, making the results of Experiment 4 similar to other demonstrations of explicit location-based inhibition (Chao, 2010;Munneke et al, 2008), while extending these results by demonstrating a limitation in the number of locations that can be simultaneously suppressed. The fact that observers would adopt such an inefficient strategy strongly suggests that they were unable to explicitly tap into a purely feature-based inhibitory mechanism, even though such a mechanism does exist and is used implicitly in certain situations (e.g., the distractor-previewing effect).…”
Section: Inhibition Of Features and Locationssupporting
confidence: 81%
“…Munneke et al found less interference from these lowercase letters on cued than on neutral trials, indicating that participants were actively inhibiting processing of the letter at the to-be-ignored location. Chao (2010) found converging evidence for speeded response times when participants were cued to ignore a specific nontarget location (although Chao did not replicate Munneke et al's finding of reduced interference from distractor letters at those locations), and several other studies have provided evidence that cueing participants to ignore or inhibit nontarget locations can speed search (Ruff & Driver, 2006;Serences, Yantis, Culberson, & Awh, 2004;Van der Stigchel, Heslenfeld, & Theeuwes, 2006).…”
mentioning
confidence: 92%
“…In a number of studies, researchers have examined what happens to distractors when participants are informed of their locations prior to the appearance of the display, showing that such preknowledge actually produces perceptual inhibition at the distractor locations (e.g., Chao, 2010;Munneke, Van der Stigchel, & Theeuwes, 2008;Ruff & Driver, 2006). These studies have shown that target processing is improved when distractor locations are known in advance, leading to the conclusion that distractor locations are inhibited.…”
Section: Resilience Of the Awb Effectmentioning
confidence: 99%
“…In fact, studies that did not permit the omitting of a cued distractor location from the search array have not shown any indication of inhibition. In Chao (2010), as well as in Buckolz, Guy, Khan, and Lawrence (2006), participants were cued with one of four display locations as the location of the distractor with 67% validity. The target could still appear in any of the four display locations with equal probability.…”
Section: Resilience Of the Awb Effectmentioning
confidence: 99%
“…A number of studies have demonstrated top-down inhibitory effects in central cueing tasks where targets are presented with distractor stimuli (Chao, 2010;Lahav, Makovski, & Tsal, 2012;Moher & Egeth, 2012;Munneke, van der Stigchel, & Theeuwes, 2008;Tsal & Makovski, 2006). In these studies, cues that signal the location of a distractor facilitate the processing of a target presented elsewhere.…”
Section: Introductionmentioning
confidence: 99%